Guild structure of stored grain insects reflects food resource availability in tropical forest ecosystems. (March 2022) - Naveena, Nadur Lakkanna; Subramanya, Suryanarayana; Setty, Siddappa
Abstract: The Guild concept has been of great interest to ecologists, and widely applied in entomology, particularly to study the activity of insects in various ecosystems. However, the guild concept in storage entomology is understudied. We hypothesized that the feeding guild structure of stored grain insect (SGI) community changes with different food resources available. In the present study, we examined the community structure of insects in the tribal grain storage system. Further, we established a classification system for the stored grain insect species based on their food resource exploitation pattern and the role of associated factors involved in the spatial and temporal structure of the SGI community. The species richness showed that cereal feeder was dominated in tribal grain storage system, abundance varied greatly, and high number of pulse feeders reflect the availability of resources. Further, it shows non-significant association among the number of species in each feeder community at different altitudes of the study area and SGI from different feeding guilds were randomly distributed, however, congregated more on their preferred food sources. Highlights: The guild concept in storage entomology is understudied. Guild structure of stored grain insects reflects availability of food resources. Species richness showed that cereal feeder guild was dominated in tribal grain storage system. SGI diversity and dominance data can be utilized for infestation control.